THE ROLE OF THE SCIENTIFIC HERITAGE OF CENTRAL ASIAN SCIENTISTS IN THE EDUCATION OF HIGHLY SPIRITUAL YOUTH - Nazarov Sardorbek (American Journals, 2024)
This article examines the role of thinkers who played a key role in the national culture of the peoples of Central Asia in the moral education of the younger generation through their scientific heritage and their importance in their high spirituality.
Keywords: People, history, education, heritage, culture, enlightenment, scientist.